Charge and adsorption height dependence of the self-metalation of porphyrins on ultrathin MgO(001) films. Issue 46 (22nd November 2022) - Presel, Francesco; Kern, Christian S.; Boné, Thomas G.; Schwarz, Florian; Puschnig, Peter; Ramsey, Michael G.; Sterrer, Martin
Abstract : While the self-metalation of 2H-TPP on MgO(001) thin films is mediated by charge transfer, 2H-P self-metalates irrespective of its charge state. The different reactivity is explained based on the molecule-substrate distance. Abstract : We have experimentally determined the adsorption structure, charge state, and metalation state of porphin, the fundamental building block of porphyrins, on ultrathin Ag(001)-supported MgO(001) films by scanning tunneling microscopy and photoemission spectroscopy, supported by calculations based on density functional theory. By tuning the substrate work function to values below and above the critical work function for charging, we succeeded in the preparation of 2H-P monolayers which contain negatively charged and uncharged molecules. It is shown that the porphin molecules self-metalate at room temperature, forming the corresponding Mg–porphin, irrespective of their charge state. This is in contrast to self-metalation of tetraphenyl porphyrin (TPP), which occurs on planar MgO(001) only if the molecules are negatively charged. The different reactivity is explained by the reduced molecule-substrate distance of the planar porphin molecule compared to the bulkier TPP. The results of this study shed light on the mechanism of porphyrin self-metalation on oxides and highlight the role of the adsorption geometry on the chemical reactivity.